Loan repayment performance and its determinants: Evidence from micro and small enterprises operating in Dire-Dawa, Ethiopia - Yitbarek Weldegerima Kiros (Journal of Innovation and Entrepreneurship, 2023)
Microfinance Institutions (MFIs) reach a large number of poor people who are not served by formal financial institutions and have been a prime element in the economic growth of countries like Ethiopia. To operate successfully MFIs have to make sure that the loan disbursed has to be repaid to have a sustainable and viable financial operation and contribute their own its share in reducing unemployment and poverty reduction. In light of this, this research study was conducted to investigate the factors affecting loan repayment performance and factors affecting it in Micro and Small Enterprises (MSEs) financed by Microfinance Institutions by taking lender characteristics. Primary data was collected using questionnaires and interviews. A total of 175 Micro and Small Enterprises were selected using purposive sampling. Secondary data was acquired from annual reports and financial statements of Microfinance institutions and other institutions. Descriptive analysis as well as econometric analysis was used to analyze the effect of the literature-driven variables on the loan repayment performance of borrowers. The binary logistic regression result revealed that loan repayment period, grace period, and timeliness of loan release have a statistically significant effect on the loan repayment performances of borrowers. Loan size has a statistically insignificant effect on the loan repayment performance of borrowers.
Keywords: 650; Ethiopia; Loan repayment performance; Logistic regression; Microfinance; MSEs